Myocardial infarction with simultaneous anterior and inferior ST‐segment elevation - Anna Meta Dyrvig Kristensen (Clinical Case Reports, 2019)
Key Clinical Message Infarction of the anterior myocardial wall results in anterior ST‐elevation. However, ST‐deviation may also appear inferiorly and may aid in localizing the culprit lesion.